Comparison of the external load of professional goalkeepers in different weekly training sessions - Casamichana, D.; Barba, E.; Martín-García, A.; Ulloa, I.; Nakamura, F. Y.; Castellano, J. (Biology of Sport, 2024)
The aim of this study was to compare the external load of professional goalkeepers (GKs) in different training sessions of the microcycle. Three professional GKs (age: 28.1±6.9 years; stature: 190.1±1.9 cm; body mass: 84.8±1.1 kg) were monitored by GPS devices during different training sessions according to the days since/until the match day (MD) at MD+1, MD-4, MD-3, MD-2 and MD-1. Different external load measures were calculated: total distance, distance covered at > 14 km· h-1, acceleration load, player load, number of dives, dive load, number of explosive efforts of displacement, number of low intensity (< 0.3 m), medium intensity (0.3-0.4 m), high intensity (> 0.4 m) and medium-high intensity jumps (> 0.3 m). The results showed that there is a decrease in the external load as the GKs` training sessions approach the match, with the lowest value of external load observed at MD-1, and the highest external loads at MD+1 and MD-4. This analysis of the external load demands of professional soccer GKs provides new information that will be useful to inform professionals when planning and implementing training and/or recovery strategies for soccer GKs during the microcycle.